The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/jp022193d
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component System Cycloheptanol (C7) + Cyclooctanol (C8):  An Extraordinary System

Abstract: The two-component system cycloheptanol (C7) + cyclooctanol (C8) has been studied by means of thermal analysis, X-ray powder diffraction, and dielectric spectroscopy. In a first step, the polymorphism of pure C7 and C8 has been revised, and new unpublished crystallographic data of the stable phases have been reported. Evidence for the isomorphism relationship between the simple cubic (SC) phases of both of the pure components has been seen through the continuous evolution of the lattice parameters, the continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 39 publications
(63 reference statements)
3
56
1
Order By: Relevance
“…Stable polymorphism C 7 -OH is one of the cyclic alcohols which exhibits the most complicated polymorphism, due to the existence of a great amount of metastable phases. From an earlier work [27], it seems to be clear that three different solid phases (denoted on cooling from the liquid state as I, II and III) could be identified down to about 170 K. Their transition temperatures (earlier consigned in Table 1 of the Ref. [27]) seem to be consistent with those obtained from several experimental techniques, in previous published works [21][22][23]25].…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Stable polymorphism C 7 -OH is one of the cyclic alcohols which exhibits the most complicated polymorphism, due to the existence of a great amount of metastable phases. From an earlier work [27], it seems to be clear that three different solid phases (denoted on cooling from the liquid state as I, II and III) could be identified down to about 170 K. Their transition temperatures (earlier consigned in Table 1 of the Ref. [27]) seem to be consistent with those obtained from several experimental techniques, in previous published works [21][22][23]25].…”
Section: Resultssupporting
confidence: 74%
“…From an earlier work [27], it seems to be clear that three different solid phases (denoted on cooling from the liquid state as I, II and III) could be identified down to about 170 K. Their transition temperatures (earlier consigned in Table 1 of the Ref. [27]) seem to be consistent with those obtained from several experimental techniques, in previous published works [21][22][23]25]. Preliminary X-ray diffraction experiments [27] revealed that phase I is simple cubic with a unit-cell parameter of 11.54(1) Å at 273 K (Z = 8) and phase II is tetragonal with unit-cell parameters of a = 19.487(2) Å and c = 11.7805(2) Å at 248.15 K (Z = 24).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations